Chronic obstructive pulmonary disease mortality, a competing risk analysis. (25th October 2018) - Abukhalaf, Jawad; Davidson, Ross; Villalobos, Nicolas; Meek, Paula; Petersen, Hans; Sood, Akshay; Tesfaigzi, Yohannes; Vazquez Guillamet, Rodrigo
Abstract: Background: Current risk factors for Chronic Obstructive Pulmonary Disease mortality focus only on overall and respiratory death. We investigated whether risk factors for each specific cause of mortality are different depending on the outcome under consideration. Methods: This retrospective cohort study included patients with a clinical diagnosis of COPD, older than 40, greater than 20 pack‐years smoking history, and obstructive pattern on spirometry. Collected data included baseline spirometry, comorbidities, medication use, tobacco exposure, severe exacerbations, and cause‐specific mortality. Results: This 512 patient cohort of heavy smokers included 277 (54.1%) males, was on average 66.4 ± 9.4 years of age and primarily non‐Hispanic white, 395 (83.2%). The average FEV1% was 52.1% (SD = 16.9%) and the median COTE score was 2 (IQR: 0‐6). A total of 67 deaths were of respiratory causes in 26 patients (38.8%), malignancies in 21 (31.1%), cardiovascular causes in 6 (9%), and from other etiologies in 14 patients (20.1%). COTE index, low predicted FEV1%, and lower body mass index were significant predictors of overall mortality. Predictors of respiratory deaths were significantly impacted by lower FEV1%, history of COPD exacerbations, lower BMI, and higher number of pack‐years smoked. Risk factors for all other cause‐specific mortality combined included history of malignancy or cardiovascular disease and smoking status. Conclusion: Cause‐specific mortality risk factors differ in patients with COPD.